2017
DOI: 10.3892/or.2017.6002
|View full text |Cite
|
Sign up to set email alerts
|

Reversal effect of adenovirus-mediated human interleukin 24 transfection on the cisplatin resistance of A549/DDP lung cancer cells

Abstract: Interleukin-24 (IL-24) is a tumor-suppressor gene that has been documented in human melanoma cells. IL-24 has marked antitumor activities on various types of human cancer, but its underlying mechanism remains unclear. In the present, we investigated the effects of human IL-24 (hIL-24) on the chemotherapy resistance of lung cancer cells. The cisplatin (DDP)-resistant lung carcinoma cell line A549/DDP was subjected to adenovirus-mediated transfection with the human IL-24 gene (Ad-hIL-24). The growth-inhibitory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Apoptosis analysis was performed as described previously [ 32 ]. Briefly, 1 × 10 4 cells of shscramble-HCT116, shMNAT1 # 1-HCT116, shMNAT1 # 2-HCT116, pSIN-HEK293T, and pSIN-MNAT1-HEK293T were seeded on six-well plates and cultured to reach 70% confluence, and were treated with 10 or 80 μg/ml 5-fluorouracil (5-FU).…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis analysis was performed as described previously [ 32 ]. Briefly, 1 × 10 4 cells of shscramble-HCT116, shMNAT1 # 1-HCT116, shMNAT1 # 2-HCT116, pSIN-HEK293T, and pSIN-MNAT1-HEK293T were seeded on six-well plates and cultured to reach 70% confluence, and were treated with 10 or 80 μg/ml 5-fluorouracil (5-FU).…”
Section: Methodsmentioning
confidence: 99%
“…29,30 In the current study, regarding GFP expression, adenoviral vectors have high transduction efficiency, which reduces the dose of the viral vector and increases therapeutic safety, consistent with the findings of previous studies. 31,32 To make a biological assessment of Ad-LAMA3 in vitro, we selected HaCaT cells. First, the viability of HaCaT cells for Ad-LAMA3 treatment was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we unexpectedly found that WT1 overexpression could significantly upregulate IL-24 in RCC by RNA-Seq analysis, and the result was confirmed by RT-qPCR and ELISA. Several studies have shown that IL-24 can selectively block proliferation by promoting G2/M arrest in many tumor cells, such as breast, lung, and liver cancer cells [ 20 , 26 , 27 ]. To investigate whether WT1's actions on proliferation are mediated by the upregulation of IL-24, we used flow cytometry to assess the effects of IL-24 in RCC cells, showing that its overexpression induced G2/M arrest and thus that a WT1/IL-24/G2/M-phase arrest regulatory axis exists in RCC cells.…”
Section: Discussionmentioning
confidence: 99%